2013
DOI: 10.1074/jbc.m113.460543
|View full text |Cite
|
Sign up to set email alerts
|

UDP-N-acetylglucosamine Transporter (SLC35A3) Regulates Biosynthesis of Highly Branched N-Glycans and Keratan Sulfate

Abstract: Background: Knowledge regarding UDP-N-acetylglucosamine transporter (NGT; SLC35A3) is incomplete due to the lack of NGT-deficient model cell lines. Results: The siRNA approach showed that NGT silencing reduces branching of complex N-glycans and keratan sulfate synthesis. Conclusion: NGT function may be coupled to the specific glycosylation pathway(s) of particular macromolecules. Significance: Our results add to the understanding of glycosylation, one of the basic posttranslational modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 38 publications
7
64
3
Order By: Relevance
“…The first finding describes an association between UDP-galactose:ceramide galactosyltransferase and UGT (14). The second report, coming from our laboratory, showed that NGT is in close proximity to Mgat5 (15). However, both findings refer to the experiments performed only on overexpressed proteins.…”
Section: Resultscontrasting
confidence: 38%
See 4 more Smart Citations
“…The first finding describes an association between UDP-galactose:ceramide galactosyltransferase and UGT (14). The second report, coming from our laboratory, showed that NGT is in close proximity to Mgat5 (15). However, both findings refer to the experiments performed only on overexpressed proteins.…”
Section: Resultscontrasting
confidence: 38%
“…Recently, it has been discovered that NSTs are also able to form heterologous complexes (13). Moreover, there are two reports on the interactions between NSTs and respective glycosyltransferases (14,15). However, in both cases, the results were derived from overexpression experiments.…”
mentioning
confidence: 53%
See 3 more Smart Citations